'We will take care of you': Identity categorisation markers in intercultural medical encounters. (August 2021) - Fantasia, Valentina; Zucchermaglio, Cristina; Fatigante, Marilena; Alby, Francesca
Ethnomethodology research has systematically investigated discursive practices of categorisation, looking at the various ways by which social actors ascribe both themselves and others to identity categories to accomplish various kinds of social actions. Drawing on a data corpus of oncological visits collected in an Italian hospital, involving both native and non-native patients, the present work analyses how participants in these intercultural medical encounters invoke and make relevant social identity categories by the marking of collective pronouns in their talk. Our results showed that whilst institutional identities (e.g. those of the doctors, the local hospital or the Tumour Board) prevailed, categorial formulations related to cultural or linguistic identities were rarely displayed in interactions with non-native patients. Conversational participants made very little of their linguistical or cultural background and when they did so, their cultural and linguistic identities were deployed for rhetorical and pragmatical aims, such as testing and negotiating common knowledge and epistemic authority. This study shows how even speakers' minimal lexical choices, such as marked pronouns, impact the negotiation of meanings and activities in life-saving sites such as oncological visits.